Appropriate Use of Inpatient Erythropoiesis Stimulating Agents - Chenghao Cui; Timothy Nguyen; Mohammad Rattu (INNOVATIONS in Pharmacy)
Background: Anemia is a significant global public health issue, and it is associated with lethargy, weakness, tiredness, and shortness of breath. Erythropoietin stimulating agents (ESAs) are recombinant / synthetic erythropoietin and can increase hemoglobin (Hb) levels. There are increased risks of cardiovascular events and death associated with the use of ESAs when raising Hb levels above 12 g/dL.